(untitled) - Everett, Nicholas (Cambridge, 2003)
This book examines the evidence for literacy in early medieval Italy under the rule of the Lombards, the last of the barbarian invaders who established a kingdom in north and central Italy from 568 to 774. By examining different kinds of written documentation (legislation, charters, inscriptions and manuscripts), the study reveals that Lombard Italy actually possessed a relatively sophisticated written culture prior to the so-called Carolingian Renaissance of the ninth century.
Keywords: Written communication,Viết; History; Italy